2017
DOI: 10.15252/emmm.201708076
|View full text |Cite
|
Sign up to set email alerts
|

An oligoclonal antibody durably overcomes resistance of lung cancer to third‐generation EGFR inhibitors

Abstract: Epidermal growth factor receptor (EGFR) mutations identify patients with lung cancer who derive benefit from kinase inhibitors. However, most patients eventually develop resistance, primarily due to the T790M second‐site mutation. Irreversible inhibitors (e.g., osimertinib/AZD9291) inhibit T790M‐EGFR, but several mechanisms, including a third‐site mutation, C797S, confer renewed resistance. We previously reported that a triple mixture of monoclonal antibodies, 3×mAbs, simultaneously targeting EGFR, HER2, and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
73
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 53 publications
1
73
0
1
Order By: Relevance
“…The third-generation EGFR-TKI osimertinib enhances both progression-free (44) and overall survival (45) compared to first generation EGFR-TKIs and is now considered first-line treatment in EGFR-mutated NSCLC. Osimertinib resistance often develops via activation of parallel RTK pathways (7)(8)(9), and broad inhibition RTK signaling may enhance osimertinib efficacy and delay therapeutic resistance. Here, we demonstrate that inhibition of the common RTK signaling intermediate SOS1 using BAY-293 showed marked synergy with osimertinib in 3D spheroid-cultured EGFR-mutated NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The third-generation EGFR-TKI osimertinib enhances both progression-free (44) and overall survival (45) compared to first generation EGFR-TKIs and is now considered first-line treatment in EGFR-mutated NSCLC. Osimertinib resistance often develops via activation of parallel RTK pathways (7)(8)(9), and broad inhibition RTK signaling may enhance osimertinib efficacy and delay therapeutic resistance. Here, we demonstrate that inhibition of the common RTK signaling intermediate SOS1 using BAY-293 showed marked synergy with osimertinib in 3D spheroid-cultured EGFR-mutated NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike first-generation EGFR-TKIs, mechanisms driving osimertinib resistance are more variable, including both EGFR-dependent (10-30%) and EGFR-independent mechanisms (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preventing this by means of a triple combination of mAbs to EGFR, HER2 and HER3 (hereinafter, 3XmAbs) arrested cell growth, sorted the three receptors for degradation, and robustly inhibited tumor growth in animal models. More recently, we demonstrated that 3XmAbs not only nullified osimertinib resistance in animal models, but it also synergized with subtherapeutic doses of this TKI (19).…”
Section: Introductionmentioning
confidence: 91%
“…The authors previously reported that a combination of three mAbs against EGFR, HER2, and HER3 suppressed compensatory feedback loops triggered by targeting EGFR alone, and markedly reduced the growth of xenografts of erlotinib-resistant PC9ER cells that harbor both an EGFR exon 19 deletion and EGFR T790M 3. They subsequently demonstrated that a similar triplet of mAbs promoted degradation of all three receptors, induced cellular senescence, and overcame resistance to osimertinib in cells with an established EGFR C797S mutation (4). Relapsed outgrowth of PC9ER xenograft tumors was seen after discontinuation of osimertinib administered at doses high enough to eradicate measurable tumors but lower than levels corresponding to therapeutic doses in human patients, but no outgrowth was observed when the triplet of antibodies was added to the same subtherapeutic doses of osimertinib.…”
mentioning
confidence: 99%